Non-isocyanate polyurethane (NIPU) based on rubber seed oil synthesized via low-pressured carbonization reaction - R.A. Raden Siti Amirah,; M.A. Faiza,; A. Zuliahani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Epoxidised rubber seed oil (ERSO) was successfully synthesized into non-isocyanate polyurethane via carboxylation method whereas peroxoformic acid was formed by in-situ reaction for epoxidation. The effects of temperature and ratio of hydrogen peroxide and formic acid to rubber seed oil carboxylation were studied. The optimum temperature for the epoxidation reaction was found at 50 °C to avoid ring opening reaction of epoxy whilst the optimum ratio of hydrogen peroxide and formic acid is equal molar of double bond: formic acid at 1:2 and 1:1, respectively. At a lower concentration of hydrogen peroxide and formic acid, the oxirane ring was stable due to the lower hydrolysis (oxirane cleavage) of an epoxide. The effect of using low content of formic acid tends to minimize unwanted epoxide ring opening to occur and make the epoxidation rate increased with increasing of oxirane number. Fourier transform infrared (FTIR) spectral displayed the presence of an epoxy functional group at 822 cm-1 and the disappearance of double bond peak at 3011 cm-1 corresponding to epoxidised oil and carbonyl group confirmed the epoxidation reaction had taken place. 1H-NMR was used to confirm the formation of carboxylate functionality after the reaction of epoxy at δ 4.83 and 4.61 ppm. In conclusion, ERSO has great potential to be used as a precursor in producing environmentally friendly non-isocyanate polyurethane.